In vitro antimicrobial action of extracts glicolics of Psidium guajava L., Syzygium cumini L. and Pimpinella anisum L. - Pereira, Cristiane Aparecida (2009)
Several researches have been developed to search for new antimicrobial agents from plants, to be used in pharmaceutical products. The aim of this study was to evaluating in vitro antimicrobial properties of extracts glicolics (75%) of Psidium guajava L. (guava), Syzygium cumini L. (jambolan) and Pimpinella anisum L. (herbsweet) on standard strains of Candida albicans, Enterococcus faecalis, Staphylococcus aureus, Streptococcus mutans, Escherichia coli and Bacillus atrophaeus (spores). During the experiment, the minimal inhibitory concentration (MIC) was determined by broth dilution method, following by subcultivation in agar in order to determine the minimal microbicide concentration (MMC). The extracts showed the following CIM and MMC, respectively: Psidium guajava L 25% and 50% for C. albicans, E. faecalis and E. coli, 12.5% and 25% for S. mutans, and 3.12% and6.25% for S. aureus; Syzygium cumini L. 25% and 50% for C. albicans, 12.5% and 25% for E. faecalis and S. aureus, and 6.25% and 12.5% for E. coli and S. mutans; Pimpinella anisum L -12.5% and 25% for C. albicans and S. mutans,6.25% and 12.5% for E. faecalis and S. aureus, and 3.12% and 6.25% for E. coli. It could be concluded that, despite the resistance by B. atrophaeus, the extracts used showed antimicrobial potential on the other microorganisms.